ASUH ORANGTUA TUNANETRA TERHADAP ANAK NORMAL DI PEKANBARU - Jenny Widiya Casih Purba; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to discover blind parent’s parenting toward normal children in Pekanbaru. Blind parent’s parenting toward normal children in Pekanbaru was analyzed through qualitative analysis. In collecting the data, the researcher used interview method to three respondents. This research is also equipped with photo. Instrument used in this research are interview guidance and is equipped with a video recorder as well as field notes.The results showed that the tendency of blind parent’s parenting toward normal children is a democratic parenting, which is developing the openness of expression, freedom of responsible choices and decisions and do not use punishment to a fault, but the advice. Limitations in the parenting process are in the protection and surveillance functions overcome by teaching self-reliance, responsibility and communication attitude and giving confidence to the child, including the modification of the environment around. While limitations in support of learning activities for children is overcome by giving encouragement to children to be independent and by having of private teachers.The key words: Parenting, Blind Parent, Normal Children